[Construction on Hot Water Conduit] - Streng, Evelyn Fiedler (1975)
Photograph of construction on a hot water conduit. The orange and yellow pipe sits in a stone box at the bottom of the photograph. Surrounding the stone outer shell is mounds of brown dirt covered in rood, tools, and metal pieces. A ladder sits against a white, flat box at the top of the photograph.